Analysis of distributed generation operation modes using new effective voltage stability index in radial system. (16th September 2013) - Jamian, J. J.; Musa, H.; Mustafa, M. W.; Mokhlis, H.; Adamu, S. S.; Chiang, Hsiao‐Dong; Tong, Jianzhong; Wang, Chengshan
SUMMARY This paper presents detail assessment of the impact of renewable energy type distributed generation operation modes on the voltage stability indices. Most of renewable distributed energy sources are capable of operating in two modes, which are constant voltage and constant power modes. Different simulation results were obtained for voltage stability index (VSI), which serves as indicator of stability. Furthermore, this study has also considered charging station (CS) as a load, that is, gradually increased at the selected bus until the system attains instability state. The persistence of the instability can lead to voltage collapse, and VSI value can give an indication of the collapse as well. In this paper, the concept of active power voltage stability index (P‐VSI) is introduced with the aim of predicting the voltage collapse as a result of incremental CS loading in the network. Based on the analysis conducted in radial networks with multiple distributed generation units, the P‐VSI gave better indication for the voltage collapse much more than reactive power voltage stability index. The analysis was conducted on 33 bus distribution system. Copyright © 2013 John Wiley & Sons, Ltd.